Application of the four-dimensional lattice spring model for blasting wave propagation around the underground rock cavern - Hu, X.; Zhao, G.; Deng, X.; Hao, Yifei; Fan, L.; Ma, G.; Zhao, J. (Pergamon, 2018)
This paper studies the propagation and attenuation of blasting wave induced by explosion in underground rock cavern by employing the newly developed four-dimensional lattice spring model (4D-LSM). The non-reflection viscous boundary condition was implemented in the 4D-LSM to reduce the computing resources of full-scale simulation of blasting wave propagation in the practical engineering. Then, a number of damping models were developed and implemented in the 4D-LSM to describe the attenuation of blasting wave in the rock mass. In addition, the influence of the loading form of blast load and damping models on the propagation and attenuation of blasting wave were studied by comparing with the field test data in details. It was found that the loading form of a triangular blast stress wave with an equivalent pressure wave and the coupled damping model could lead the 4D-LSM producing a reasonable fitting over the field test data in terms of both the blasting waveform recorded at a given measuring point and attenuation results from a number of measuring points. Our study provides a basis for the further application of the 4D-LSM as an alternative numerical tool in modeling the blasting wave propagation problems in rock engineering.